Hydrothermal Leaching of Silver and Aluminum from Waste Monocrystalline and Polycrystalline Photovoltaic Panels - Eleni Kastanaki; Emmanouel Lagoudakis; Georgios Kalogerakis; Apostolos Giannis (Applied Sciences, 2023)
The aim of this study was to investigate the hydrothermal leaching of silver and aluminum from waste monocrystalline silicon (m-Si) and polycrystalline silicon (p-Si) photovoltaic panels (PV) from both cells and metal ribbons using mild HNO3 solutions. Prior to leaching, pretreatment was applied to remove the fluoropolymer backsheet and thermally degrade the ethyl vinyl acetate (EVA) polymer. Several hydrothermal parameters were investigated, such as the liquid-to-solid (L/S) ratio, HNO3 concentration (N), time (t) and temperature (T). Based on preliminary tests, the HNO3 concentration was set in the range of 1–2 N to reduce hazardous waste effluents. The response surface methodology (RSM) was applied to optimize the hydrothermal leaching parameters. It was found that processing time was the most important factor for Ag leaching, followed by HNO3 concentration and L/S ratio, while the processing temperature (100–140 °C) was not a statistically significant factor. Aluminum leaching was efficient under most hydrothermal conditions. For comparison, leaching was also applied at lower temperatures of 25–45 °C for prolonged times; however, lower efficiencies were observed. Under the optimal hydrothermal conditions, Ag can be completely leached, while Al dissolution was favored at hydrothermal conditions compared with lower temperature leaching. Silver leaching efficiency was 100% under hydrothermal conditions; however, under conventional lower temperature conditions, it was 80.7–85.3% for m-Si and p-Si waste panels. Under conventional lower temperature conditions, Al leaching efficiency was 56.6–61.3% for p-Si and m-Si waste panels.